ANALISIS GENDER PADA PENGELOLAAN HUTAN OLEH MASYARAKAT DAYAK MERATUS (Studi Kasus di Desa Loklahung Kecamatan Loksado Kabupaten Hulu Sungai Selatan) - Raudhah, Raudhah; Satriadi, Trisnu; Hafianor, Hafizianor (Jurnal Hutan Tropis, 2025)
The modern era now opens up wide and open opportunities for women to develop their potential in all fields to the maximum, of course it has shifted the role of women from previously only domestic roles to now expanding to public roles. The role og managing forests, which was previously considered the job of men only, has now changed, evenone the who led Ministry of Forestry in regulating all forestry and environmental policies during the two terms of President Jokowi’s administration was a women. The role of managing forests is not only carried out by men but also women, this is even provenby the many successes of women in managing forests. Based on 2015 KLHK data, Mollo women in Fatumnasi Village, NTT, women carried out a peaceful weaving movement to save the environment from the marble mining industry. Kenyan women have also, throught the greenbelt movement, since 1997 planted more than 40 million trees and employed 80.000 people in nurseries to ensure a sufficient stock of trees for reforestation and improving the women’s economy. Forest management in Loklahung village is carried out by the Dayak Meratus community, both men and women in the form of farming activities, cinnamon gardening, and haunting and gathering forest products. This research aims to analyze the role of women and men in decision making on forest activities in Loklahung Village, Loksado District, HSS Regency. The object of research is the Dayak Meratus Community of Loklahung Village whose activities are farming, cinnamon gardening, and haunting and gathering forest products. Based on the research results, the role of decision making in forest management activities (farming, cinnamon gardening, and haunting and gathering forest product), decision making in financial matters and decision making in social and domestic family activities, are predominantly decided jointly by husband and wife. Decision making on farming activities in forest management is 73,40% decided jointly by husband and wife, 11,70% decided by husband, and 14,09% is decided by wife. Decision making in cinnamon gardening activities was 62,82% decided jointly by husband and wife, 22,56% decided by husband, and 14.62% decided by wife. Decision making in hunting and gathering and forest products is 60% decided jointly by husband and wife, 26,44% is decided by husband, and 13,46% is decided by wife. Decision making in financial matters is 45,33% decided jointly by husband and wife, 14,84% is decided by husband and 39,83% decided by wife. Decision making in social and domestic family activities by husband is 45,33% decided jointly by husband and wife, 14,84% is decided by husband and 39,83% is decided by wife.